Transcriptome and Metabolome Analysis of a Late-Senescent Vegetable Soybean during Seed Development Provides New Insights into Degradation of Chlorophyll - Jian Wang; Guang Chen; Xuetong Li; Xujun Fu; Sujuan Li; Xiaoyuan Tao; Zhong-Hua Chen; Shengchun Xu (MDPI AG, 2022)
(1) Background: Senescence represents the final stage of plant growth and development, which transfers nutrients to growing seeds and directly affects the yield and quality of crops. However, little is known about chlorophyll degradation in developing and maturing seeds, in contrast to leaf senescence; (2) Methods: RNA-Seq was used to analyze the differentially expressed genes of different late-senescent germplasms. A widely untargeted metabolic analysis was used to analyze differential metabolites. In addition, qRT-PCR was conducted to detect gene expression levels; (3) Results: Transcriptome analysis revealed that ZX12 seeds have a higher expression level of the chlorophyll synthesis genes in the early stage of maturity, compared with ZX4, and have a lower expression level of chlorophyll degradation genes in the late stage of maturity. Flavonoids were the primary differential metabolites, and ZX12 contains the unique and highest expression of three types of metabolites, including farrerol-7-O-glucoside, cyanidin-3-o-(6'-o-feruloyl) glucoside, and kaempferide-3-o-(6'-malonyl) glucoside. Among them, farrerol-7-O-glucoside and cyanidin-3-o-(6'-o-feruloyl) glucoside are flavonoid derivatives containing mono and dihydroxy-B-ring chemical structures, respectively; and (4) Conclusions: It is speculated that the two metabolites can slow down the degradation process of chlorophyll by scavenging oxygen-free radicals in the chloroplast.